Моделювання техніко-економічного розвитку кіберспорту за напрямом CS: GO та DOTA2 в Україні - Чизмар Іван; Csizmár Iván; Chyzmar Ivan (Видавничий дім «Гельветика», 2021)
Резюме. У статті представлено характеристику та здійснено системну ілюстрацію підходу до моделювання техніко-економічного розвитку кіберспорту. Передбачається, що моделювання техніко-економічного розвитку має відображати інтервали експлуатації обладнання робочих зон усіх кіберспортивних організацій у цільовій формальній групі розробника/видавця ігор. Процес дослідження здійснюється з урахуванням добору моделей техніко-економічного розвитку, що враховують потребу виконання вимог щодо якості відтворення ігор за показником fps, а саме за частотою кадрів, що знижуються під час експлуатації обладнання та навантаження на операційні системи для ігрових комп'ютерів, консолей. Процес дослідження здійснюється з урахуванням добору моделей техніко-економічного розвитку, що враховують потребу виконання вимог щодо Ping, а саме за швидкістю передачі інформації від клієнта до сервера, і навпаки. При цьому дослідження підтверджує, що моделювання процесів техніко-економічного розвитку за цільовими формальними групами розробника/видавця ігор, що є кіберспортивними дисциплінами, слід здійснювати на основі формування конкретних правил оперування процесами експлуатації та оновлення обладнання виходячи з формалізації завдання його заміни з орієнтацією на стійкість кіберспортивної організації (турнірного оператора/ арени, кіберспортивного клубу тощо).

Abstract. The article presents a description and a systematic illustration of the approach to modeling the technical and economic development of cybersport. It is assumed that the modeling of techno-economic development should reflect the operating intervals of the equipment of all cybersports organizations in the target, formal game developer/publisher group. The research process takes into account the selection of models of techno-economic development that take into account the need to meet the requirements for the quality of playback of the games in terms of fps, namely the number of frames, the lower equipment, and load on operating systems for game computers, cyber consoles, and current game modifications. The research process is carried out taking into account the selection of techno-economic development models taking into account the need to meet the requirements of Ping, namely the speed of information transfer from the client to the server and vice versa. At the same time, the study confirms that the study of techno-economic development processes by target formal groups of game developers/publishers, which are cybersports disciplines, should be implemented through the establishment of specific operating rules for the operation and renewal of equipment, based on the formalization of the task of replacing it with a focus on the sustainability of the development of the cybersports organization (tournament) operator having arenas, cybersports club, etc.). For the direct commissioning of equipment, the possible state of a medium-income function must be determined for each operating step. A model for the technical and economic development of cybersports organizations should also be formalized based on functional equations. The preferred type of functional equation is the one with the retention of equipment. To optimize the technical and economic development model of TFF Valve Corporation, we believe that the main emphasis should be placed on developing a common methodological approach to formalizing its technical and economic development. Further prospects in this direction lie in the application of an approach to defining directions of optimization of technical and economic development for all target formal groups of game developers/ publishers developed in Ukraine.
Modeling the techno-economic development of cybersport in the direction CS:GO and DOTA2 in Ukraine
Редакційна колегія: http://bses.in.ua/uk/editorial-staff
Зміст: http://bses.in.ua/uk/72-2021
Keywords: кіберспорт; техніко-економічний розвиток; розробник/видавець ігор; віртуальний простір; cybersport; techno-economic development; game developer/publisher; virtual space